Performance Attribution using an APT with Prespecified Macrofactors and Time-Varying Risk Premia and Betas - Kryzanowski, Lawrence; Lalancette, Simon; To, Minh Chau (Journal of Financial and Quantitative Analysis, 1997)
Lawrence Kryzanowski, Simon Lalancette, Minh Chau To, Performance Attribution using an APT with Prespecified Macrofactors and Time-Varying Risk Premia and Betas, The Journal of Financial and Quantitative Analysis, Vol. 32, No. 2 (Jun., 1997), pp. 205-224